Clinical risk factors of recurrent kidney stone disease: a cohort retrospective study in a tertiary referral hospital - Atmoko, Widi; Febriyani; Savitri, Ary Indriana; Uiterwaal, Cuno; Setiati, Siti; Hamid, Agus Rizal Ardy Hariandy; Birowo, Ponco; Rasyid, Nur (Faculty of Medicine Universitas Indonesia, 2023)
BACKGROUND Nephrolithiasis or kidney stone disease (KSD) is common worldwide. Despite various effective treatment strategies, KSD recurrence remains a problem. This study aimed to investigate the risk factors of KSD recurrence. METHODS This retrospective cohort study used medical records of all patients who came to the Department of Urology, Cipto Mangunkusumo Hospital, Jakarta, from January 2014 to December 2019, with asymptomatic and symptomatic KSD. Demographic information, clinical data, exposure to risk factors, and recurrent KSD diagnosis were collected. Univariate and multivariate analyses using logistic regression were performed to determine the significant risk factors. RESULTS We reported 325 patients with a median age of 52 years. More than half of the patients were males and from Java. Staghorn stone dominated the KSD types found in 181 patients (55.7%). After undergoing percutaneous nephrolithotomy, 214 patients (65.8%) became stone-free. However, about 40.6% of them later developed recurrent KSD. The adjusted odds ratio in recurrent KSD were 1.46 (95% confidence interval [CI] 1.33–1.59) for younger age, 1.86 (95% CI 1.61–2.07) for overweight–obese, 2.13 (95% CI 1.89–2.31) for less fluid intake, 1.81 (95% CI 0.97–2.12) for routine tea consumption, 1.24 (95% CI 1.06–1.84) for routine vegetables consumption, 2.27 (95% CI 1.83–2.84) for a family history of KSD, and 2.08 (95% CI 1.77–2.39) for diabetes mellitus (DM). CONCLUSIONS Most patients with recurrent KSD were younger, overweight/obese, had less fluid intake, a family history of KSD, and DM. Modifying a healthy lifestyle and a balanced diet is important to prevent KSD recurrence.